Facile Fabrication of Layered Double Hydroxide-Lignin for Efficient Adsorption of Malachite Green - Neza Rahayu Palapa; Nur Ahmad; Alfan Wijaya; Zaqiya Artha Zahara (Science and Technology Indonesia, 2023)
Preparation of layered double hydroxide-lignin (lignin-Zn/Al) carried out by coprecipitation method. The FTIR spectra of lignin-Zn/Al displayed at 3448, 2939, 1620, 1381, 1118, 1041, and 601 cm−1. The characteristic peaks are located at 10.1°, 19.1°, 20.1°, 29.4°, 33.9°, and 60.4°. The lignin-Zn/Al nitrogen adsorption-desorption isotherm showed a Type-IV curve, indicating that it had a mesoporous structure. The H3 kind of hysteresis loop also provides evidence for the presence of mesopores within the lignin-Zn/Al complex. Lignin-Zn/Al, lignin, and Zn/Al had pHpzc values of 6.09, 3.01, and 6.09, respectively. Lignin-Zn/Al, lignin, and Zn/Al are positively charged when the pH of the solution is less than pHpzc, and they are negatively charged when the pH of the solution is more than pHpzc. The Langmuir and pseudo-second-order model best represented the MG adsorption onto all adsorbents. The lignin-Zn/Al, lignin, and Zn/Al were shown to have maximum Langmuir adsorption capacities of 83.034, 78.740, and 36.364 mg/g, respectively. Zn/Al adsorption capacity increased 2.28 times after being composited with lignin.